Working with difficult people, second revised edition : handling the ten types of problem people without losing your mind - Hakim, Amy Cooper (Your coach in a box., 2017)
"A revised edition of the classic guide on how to best resolve conflict in today's technologically advanced workplace. Your work day is filled with them--people who frustrate, impede, maneuver, undermine, plot, connive, and whine. This indispensable guide details specific techniques for handling all of them, with easy-to-follow scenarios for every situation. Updated and revised to reflect modern issues including technology, generation gaps, and language barriers, this guide describes 10 kinds of culprits, from tyrants and bullies (regular and cyber) to the pushy and presumptuous to connivers and camouflagers; and offers helpful strategies and phrases for diffusing workplace tensions and effectively resolving conflicts."